2022
DOI: 10.1111/bjop.12597
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone use and daily cognitive failures: A critical examination using a daily diary approach with objective smartphone measures

Abstract: While smartphones have brought many benefits and conveniences to users, there is continuing debate regarding their potential negative consequences on everyday cognition such as daily cognitive failures. A few cross-sectional studies have found positive associations between smartphone use and cognitive failures. However, several research gaps remain, such as the use of cross-sectional designs, confounds related to stable individual differences, the lack of validity in self-report measures of smartphone use, mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…Despite the high correlation between ADHD and problematic smartphone use [47], a previous study reported that the adverse effects of smartphone use on attention are not remarkable in the general population [48]. A recent study also reported no impairment in the problematic smartphone use of cognitive tests evaluating executive function [49]. Another study reported that problematic smartphone users performed poorly on cognitive tests that assessed attentional control with interfering stimuli [50].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the high correlation between ADHD and problematic smartphone use [47], a previous study reported that the adverse effects of smartphone use on attention are not remarkable in the general population [48]. A recent study also reported no impairment in the problematic smartphone use of cognitive tests evaluating executive function [49]. Another study reported that problematic smartphone users performed poorly on cognitive tests that assessed attentional control with interfering stimuli [50].…”
Section: Discussionmentioning
confidence: 99%
“…Successfully addressing stress usually requires activating coping mechanisms that directly address the responsible stressor [31,66]. Therefore, to guide the development of appropriate stress interventions, many works have focused on understanding prevalent stressors and their role in PTSD [60], depression [51], anxiety disorder [11], heart diseases [53], asthma or rheumatoid arthritis [69], as well as in the general population [4,27,39]. These studies have shown that stressors predict daily symptoms and health outcomes.…”
Section: Logging and Journaling Of Stressful Events For Stress Manage...mentioning
confidence: 99%
“…Stressors have been collected at the end of day, via telephones [4], surveys [39], and smartphones [27]. More frequent collections (5-6 times daily) have resulted in more stressors reported, and hence are being adopted more widely [72].…”
Section: Logging and Journaling Of Stressful Events For Stress Manage...mentioning
confidence: 99%
“…Therefore, to provide a rigorous examination of the association between FoMO and daily emotional well-being, we aimed to utilize a daily diary approach by repeatedly measuring FoMO and emotional well-being over 7 days. The current daily diary approach would allow us to model day-to-day within-person associations between FoMO and emotional well-being to rule out any potential confounds that are stable over time (Almeida, 2005; Hartanto et al, 2022). Furthermore, the experiential sampling of FoMO and emotional well-being would increase ecological validity by allowing participants to respond in a natural rather than laboratory setting, as well as address issues related to memory distortion (Scollon et al, 2009; Stone & Shiffman, 2002).…”
Section: Literature Reviewmentioning
confidence: 99%